Adoption of the Environmental Management System (EMS) :Challenges for Sustainable Development in Algerian Agri-food Companies - Boulfoul, Nouara; Hanafi, Wassila; Mahdid, Malika; Brabez, Fatima (Indian Journal of Extension Education, 2025)
The study, conducted between January and July 2024, identified the benefits and challenges faced by fifty-three ISO 14001-certified agri-food companies in Algeria. The current study's findings indicated that implementing an Environmental Management System (EMS) can result in significant cost savings by effectively managing natural resources, reducing waste, and controlling pollution. On the other hand, the significant challenges to adopt an EMS lie in the need for more collaboration from subcontractors, the fact that the savings achieved do not offset the expenses related to the rigorous implementation of management solutions, and the increase in management and operational costs. However, the implementation process requires significant effort and financial investment, which can be a limitation for some companies withsignificant positive correlations for parameters influencing the success of the adoption of the EMS system such as lowering costs (p = 0.0000), EMS adopting costs (p = 0.0021), and EMS maintenance costs (p = 0.0112) with EMS adoption. On the other hand, managerial education level (p = 0.021) and efforts to improve product quality (p = 0.010) exhibited significant negative correlations. Composite reliability values, ranging from 0.780 to 0.990, demonstrated strong internal consistency across the constructs measured.